The gloss and the text: William Perkins on interpreting Scripture with Scripture - Ballitch, Andrew S. (Studies in historical and systematic theology, 2020)
Introduction -- Thesis -- History of Research -- Methodology -- Perkin's exegetical method -- Biographical context -- Hermeneutical context -- The Arte of Prophecying -- Exegesis in sermons and commentaries -- The True Gaine: Philippians 3:7-11 -- Galatians -- Christ's Sermon on the Mount -- The combat betweene Christ and the devill: Matthew 4:1-11 -- Revelation 1-3 -- A cloud of faithful witnesses: Hebrews 11 -- Jude -- An exhortation to repentance: Zephaniah 2:1-2 -- Exegesis in practical works -- The Christian life -- Christian ministry -- Exegesis in theological works -- Catechism -- God's sovereignty in salvation -- Exegesis in polemical works -- Polemics against the church of Rome -- The damned art of witchcraft -- Polemics against astrology.